Bank Geographic Diversification and Systemic Risk. (24th December 2019) - Chu, Yongqiang; Deng, Saiying; Xia, Cong
Abstract: Exploiting staggered interstate banking deregulation as exogenous shocks to bank geographic expansion, we examine the causal effect of geographic diversification on systemic risk. Using the gravity-deregulation approach, we find that bank geographic diversification leads to higher systemic risk measured by the change in conditional value at risk ($Δ$ CoVaR ) and financial integration ( Logistic ($R^{2}))$ . Furthermore, we document that geographic diversification affects systemic risk via its impact on asset similarity. The impact of geographic diversification on systemic risk is stronger in BHCs located in states comoving less with the U.S. aggregate economy.